Prospective comparison of transperineal magnetic resonance imaging/ultrasonography fusion biopsy and transrectal systematic biopsy in biopsy-naïve patients - Borkowetz, Angelika Sabina Maria; Tosev, Georgi; Radtke, Jan Philipp; Kesch, Claudia; Hohenfellner, Markus (BJU international, 2018)
Objectives To evaluate the value of multiparametric magnetic resonance imaging (mpMRI) in the detection of significant prostate cancer (PCa) and to compare transperineal MRI/ultrasonography fusion biopsy (fusPbx) with conventional transrectal systematic biopsy (sysPbx) in biopsy-naïve patients. Patients and Methods This multicentre, prospective trial investigated biopsy-naïve patients with suspicion of PCa undergoing transperineal fusPbx in combination with transrectal sysPbx (comPbx). The primary outcome was the detection of significant PCa, defined as Gleason pattern 4 or 5. We analysed the results after a study period of 2 years. Results The study included 214 patients. The median (range) number of targeted and systematic cores was 6 (2-15) and 12 (6-18), respectively. The overall PCa detection rate of comPbx was 52%. FusPbx detected more PCa than sysPbx (47% vs 43%; P = 0.15). The detection rate of significant PCa was 38% for fusPbx and 35% for sysPbx (P = 0.296). The rate of missed significant PCa was 14% in fusPbx and 21% in sysPbx. ComPbx detected significantly more significant PCa than fusPbx and sysPbx alone (44% vs 38% vs 35%; P < 0.005). In patients presenting with Prostate Imaging Reporting and Data System (PI-RADS) 4 and 5 lesions there was a higher detection rate of significant PCa than in patients presenting with PI-RADS ≤3 lesions in comPbx (61% vs 14%; P < 0.005). Conclusions For biopsy-naïve men with tumour-suspicious lesions in mpMRI, the combined approach outperformed both fusPbx and sysPbx in the detection of overall PCa and significant PCa. Thus, biopsy-naïve patients may benefit from sysPbx in combination with mpMRI targeted fusPbx.